Decorative Features of the Delphinium Plant - Abdukhamidovich, Nasritdinov Akhmadjon; Dilmurod’s, Yusubova Moxlaroyim (American Journal of Biodiversity, 2025)
In recent years, environmental protection and landscaping of settlements have become an important issue in adapting new trees, shrubs and flowers to local conditions. They have the property of purifying the ambient air, retaining moisture, protecting the air from pollution and cleaning it from dust. This delphinium plant is a beautiful ornamental flower, available in white, red, pink and purple colors. They are of great importance in landscaping alleys, squares, gardens and parks and shaping their landscape appearance.